Pengaruh Kemudahan Penggunaan dan Kepercayaan Konsumen Terhadap Minat Beli Tiket Kereta Api Secara Online Menggunakan Aplikasi KAI Access (Studi Kasus Pada Masyarakat Kota Bandung) - Syifa, Adinda Naila; Maulani, Terra Saptina (STIE Ekuitas, 2022)
The development of technology makes the internet and smartphones very popular among the people. Thus, the businessmen adjust the situation by presenting various internet-based services, one of which is PT. KAI that provides innovation and renewal while keeping abreast of developments in the era of globalization and digitalization as well as the needs of the free market by creating mobile e-ticketing called the KAI Access application. This study aims to determine the effect of Ease of Use and Customer Trust on Purchase Intention Train Tickets Online Using KAI Access with the people of Bandung as respondents. This research method uses quantitative methods with descriptive and verification types which aim to determine the description and influence between variables on the object under study. The sample in this study were 100 respondents from Bandung City Community. The analysis used in the test is Multiple Linear Regression and Hypothesis F Test and Hypothesis t Test. Based on the results of multiple linear regression, it is explained that Ease of Use and Customer Trust have a unidirectional relationship with Purchase Intention. The partial hypothesis test explains that Ease of Use has a significant effect on Purchase Intention and Customer Trust has a significant effect on Purchase Intention, while the simultaneous hypothesis test explains that Ease of Use and Customer Trust have a significant effect on Purchase Intention.